2001
DOI: 10.4049/jimmunol.166.11.6907
|View full text |Cite
|
Sign up to set email alerts
|

Thiopalmitoylation of Myelin Proteolipid Protein Epitopes Enhances Immunogenicity and Encephalitogenicity

Abstract: Proteolipid protein (PLP) is the most abundant protein of CNS myelin, and is posttranslationally acylated by covalent attachment of long chain fatty acids to cysteine residues via a thioester linkage. Two of the acylation sites are within epitopes of PLP that are encephalitogenic in SJL/J mice (PLP104–117 and PLP139–151) and against which increased immune responses have been detected in some multiple sclerosis patients. It is known that attachment of certain types of lipid side chains to peptides can result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 53 publications
4
37
0
Order By: Relevance
“…Several reports have indicated that N-palmitoylation of antigenic peptides can reduce T cell-dependent responses in vivo [15][16][17][18]. We show here for the first time that the mechanistic base for such an effect at the T cell clonal level is that N-palmitoylation weakens the agonist properties of the wild-type peptide.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Several reports have indicated that N-palmitoylation of antigenic peptides can reduce T cell-dependent responses in vivo [15][16][17][18]. We show here for the first time that the mechanistic base for such an effect at the T cell clonal level is that N-palmitoylation weakens the agonist properties of the wild-type peptide.…”
Section: Discussionmentioning
confidence: 62%
“…However, the N-palmitoylated version of such peptides inhibit the subsequent response not only to the native peptide (Fig. 6) but also to the thioacylated peptide [17]. The fact that PALPCC 81-104 failed to prime could be explained by virtue of being a weak agonist, but we cannot rule out the possibility that PALPCC 81-104 peptide may also induce anergy to itself.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations